God's people made new : how exploring the Bible together launched a church's spirit-filled future - Powell, Rachael J. (Fortress Press, 2022)
God's People Made New reveals the role of God's Word in forming a congregation. Through the voices of congregants, biblical texts, theological reflection, and tools for studying the Bible, Rachael J. Powell inspires congregations to enter into the power of Scripture.